Experimental and density functional theory studies of methyl orange adsorption on Ni-Al/LDH intercalated sodium dodecyl sulfate - A. Machrouhi; M. Khnifira; W. Boumya; M. Sadiq; M. Abdennouri; A. Elhalil; F.Z. Mahjoubi; N. Barka (Chemical Physics Impact, 2023)
This study examined the application of Ni-Al layered double hydroxide (Ni-Al/LDH) intercalated with sodium dodecyl sulfate (SDS) anion as an adsorbent for the elimination of methyl orange (MO) model dye from aqueous solutions. Material has been synthesized using a co-precipitation process with a molar ratio of Ni/Al of 3. XRD, FTIR, TEM/EDX and TGA/DTA were used to determine structural, morphological and thermal properties of the material. Under varied circumstances, the adsorption capability for MO dye elimination was tested in batch mode. The experimental findings demonstrate that the greatest adsorption takes place at pH levels ranging from neutral to acidic. Kinetic data were well-suited to the pseudo-second-order model. Equilibrium isotherm adsorption data were correlated to the Langmuir model with a high adsorption capacity of 808.8 mg/g. The adsorption process was exothermic and spontaneous nature. In order to analyze the adsorbate-adsorbent interaction mechanism, the anionic dye MO structure was evaluated using the Gaussian 09 W program at the B3LYP/LANL2DZ level. The quantum descriptors examined supported the experimental results obtained in this study.